ediBag / Zareef Hidayat Zulkiflee … [et al.] - Zulkiflee, Zareef Hidayat; Sukimin, Irfan Syaqir; Raja Mohd Roslan, Raja Muhammad Haikal; Huzaifah, Muhammad Amiruddin; Husain, Nor Azmawati; Ibrahim, Khalilah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Watching a movie? Orthodoxly, the go-to-movie snack would be popcorn. It is the perfect snack to munch on while watching that long awaited film. But halfway through the movie the snack will always run out and you are only left with an empty box that is just a waste of space and dangerous for the environment. And that is where edible popcorn bags will change everything. Edible popcorn bags are the sustainable concept that uses edible plastic to switch from non-consumable to consumable packages to hold the popcorn. After you done eating the popcorn then later you can start munching on the bag itself. Even if it is thrown away it is safe for the environment because it is biodegradable. With this novel innovation, recycling will be a burden in the past since the product itself is edible and if it is thrown it will just naturally decompose. The edible popcorn bag would not be restricted to only one flavor but the bag itself can be flavored to appeal to a variety of consensus. The debut of this product potentially at the cinema but the edible plastic can be used in a variety of other sector and hope that it will catch on in the future of the food industry. The goal of this innovation is to minimize plastic wastage and to create an alternative to classic plastic food packaging.